Developing sustainability index of microfinance institutions in Pakistan - Saad, Muhammad (2019)
Despite the importance of sustainable microfinance institutions (MFIs) in alleviating poverty, the measurement of sustainability is still under debate. This study aims to develop an index that measures the sustainability of MFIs in Pakistan based on a double bottom line approach. Principal Component Analysis (PCA) is employed to assign weights to individual indicators that are further used to compute the sustainability score of MFIs in Pakistan for the period 2006-2015. The weights assigned to individual indicators of financial self-sufficiency (FSS), operational self-sufficiency (OSS), average loan balance per borrower (ALPB) and a number of active borrowers (NAB) are 0.6643, 0.6607, -0.1905 and 0.2931 respectively. The positive values for weights indicate that any increase in FSS, OSS, and NAB will cause incremental sustainability scores of MFIs, whereas, an increase in ALPB will cause a reduction in sustainability scores of MFIs. The determinants of sustainability are also identified using Fixed Effect Regression. Results suggest that return on asset (ROA), return on equity (ROE), borrower per staff member (BPSM) and gross loan portfolio (GLP) have a significant effect on the sustainability of MFIs. Results found in the moderated model, using age and size as proxies of life cycle theory, further suggest that age significantly moderates the relationship between ROE, portfolio at risk greater than 30 days (PAR>30), BPSM, debt to equity ratio (DER), GLP and sustainability of MFIs. Moreover, size significantly moderates the relationship between ROA, BPSM, and sustainability of MFIs. A composite measure of sustainability developed in this study is helpful for managers to evaluate MFIs in pursuit of their efforts to achieve the double bottom line. Findings further suggest that over the life cycle of MFIs, managers need to mainly focus on ROA, ROE, and BPSM, along with PAR>30, DER and GLP to attain sustainability.